Impact of chemicals and modified atmosphere packaging (MAP) on postharvest quality of litchi cv. China - Sarkar, Animesh; Sumi , Mary (Journal of Postharvest Technology, 2023)
The efficacy of chemicals and modified atmosphere packaging were investigated in freshly harvested litchi fruit to observe the bio-chemical  changes and extension of shelf life of fruits at two days interval for a period of six days storage at ambient temperature during 2020-2021,  Department of Horticulture, SASRD, Nagaland University. The pre-cooled litchi fruits after disinfectant were emerged in CaCl2 (1% & 2%),  Wax emulsion (5% & 10%), Chitosan (1% & 2%) and Kaolin (1% & 2%) for 60 seconds. The treated fruits were packed in polypropylene  plastic (PPP) @ 6% and 9% perforation and assessed the quality attributes at two days interval. The fruits dipped in calcium chloride solution  @ 1% and 2% and wax emulsion @ 5% and also packed in polypropylene plastic @ 6% perforation showed a positive and significant impact  to maintain biochemical quality during storage. The fruits treated with calcium chloride @ 1% packed in 6% perforation polypropylene plastic  recorded maximum total soluble solids (17.62°B), total sugar (11.36%), ascorbic acid (54.48 mg/100g pulp), fruit firmness (1.90 kg cm-2),  polymeric colour retention with high anthocyanin content (49.67 mg/100g peel) in peel and the lowest acidity (0.48%) in juice at 6 days of  storage.
Keywords: Litchi; chemicals,; , MAP; quality; storage